1994
DOI: 10.1099/00221287-140-10-2657
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of thiocyanate as a nitrogen source by a heterotrophic bacterium: the degradative pathway involves formation of ammonia and tetrathionate

Abstract: A Gram-negative soil bacterium (isolate 26B) has been shown t o utilize up t o 100 mM thiocyanate as a source of nitrogen when supplied with glucose as the source of carbon and energy. During growth of isolate 26B with thiocyanate as the source of nitrogen, no ammonia, nitrate, nitrite, cyanide, cyanate, sulfate, sulfite, sulfide or carbonyl sulfide was detected in the growth medium. Growth of the bacterium on 14C-labelled thiocyanate (1.6 pCi) and glucose, yielded 14C-labelled carbon dioxide (0.9 pCi). The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…Thiocyanate utilization occurred mainly during the exponential phase of growth for both cultures. A similar result was previously reported for Arthrobacter species (4,18). Unlike the mixed culture, BMV8 strain cultures showed the formation of 1.46 mM ammonia after 36 hours of incubation.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Thiocyanate utilization occurred mainly during the exponential phase of growth for both cultures. A similar result was previously reported for Arthrobacter species (4,18). Unlike the mixed culture, BMV8 strain cultures showed the formation of 1.46 mM ammonia after 36 hours of incubation.…”
supporting
confidence: 89%
“…The mixed culture ( Fig.1-a) and the BMV8 isolated strain (Fig.1-b) were able to degrade thiocyanate heterotrophically using this compound as a nitrogen source. Most of the thiocyanate-utilizing microbes reported in the literature are autotrophs, and only few heterotrophs with ability to degrade thiocyanate have been described (1,16,18,19). In the noninoculated control medium (M9), the levels of thiocyanate did not decrease during the incubation period.…”
mentioning
confidence: 99%
“…In general, removal efficiency increased with increasing recirculation, although the lower efficiency obtained for R=2 was due to a noticeable increase in the concentration of thiocyanate in the coke wastewater. As in the case of phenols and COD, major removal is obtained in the second reactor by heterotrophic biodegradation (Kwon et al 2002;Stafford and Calley 1969;Stratford et al 1979).…”
Section: Removal Of Phenolsmentioning
confidence: 99%
“…Several neutrophilic heterotrophic bacteria (Arthrobacter sp., Pseudomonas spp., Methylobacterium thiocyanatum) able to utilize the nitrogen atom from thiocyanate were isolated from different sources which may have contained thiocyanate (2,11,28,41,42,45). It has been suggested that such bacteria employ the same primary thiocyanate degradation pathways as autotrophs (e.g., either cyanate pathways or COS pathways), but again, no direct proof of accumulation of these intermediates has been presented.…”
Section: Thiocyanate (N'cosmentioning
confidence: 99%